O financiamento da assistência social no Governo do Estado de São Paulo: período de 2004 a 2012 - Silva, Adriano Borges Domingos da (2014)
The present study analyzes the social assistance financing in the state of São Paulo s government referent to the period from 2004 through 2012. The period s selection enables us to analyze the social assistance financing in the SUAS era. Our starting point to the analysis is the approval of both the Welfare National Policy (PNAS) from 2004 and the Social Assistance Unified System Basic Operational Standard (NOB/SUAS 2012). It is essential to remember that incorporated in part of the analyzed course, is the approval of Law number 12.435 passed on July 06, 2011, which altered Law number 8.742 from December, 07, 1993, and portraits the accomplished advances with SUAS implementation. The spotlight is in the management and financing of the social assistance policy in public responsibilities perspective of assuring non-contributive social protection to the population through the SUAS. The main objective was to know the plot of public budget, public stock and budgetary cycle in social assurance public policies, specially how the social assistance financing is given in the SUAS context. The study required knowing basic concepts applied to the planning system and budgetary and financial execution, understanding the public resources management cycle which involve PPA, LDO and LOA, knowing São Paulo s government resources programming and evolution, analyzing advances, challenges and limits in the cofinancing of the social assistance right field. The working method has as its perspective the analysis and critical observation of reality and confronts normative orientations with the effective social assistance policy financing and costing execution, analyzes the expense direction inquiring the budgetary programs and the social assistance policy budgetary execution. The main data sources consulted were: Budget, Multi-annual Plan, Budgetary Guidelines Law, State s General Audit and Budgetary Execution by Executive. The results are known by this policy actors, however evidenced based on official data from the own government. It is noticed that, nine years after SUAS approval, São Paulo State s government perform social assistance double command, the invested percentage is low compared with the existing demands and structural exigencies from social assistance services. Programmatic option for SEDS, inserted in the budgetary pieces, has been investment in transversal policies and ends up representing limited investment (less than half percent of expenses executed by State s budget) in the objectification of SUAS state management